Intra-breath changes in respiratory mechanics are sensitive to history of respiratory illness in preschool children: the SEPAGES cohort - Siroux, Valérie; Boudier, Anne; Lyon-Caen, Sarah; Quentin, Joane; Gioria, Yoann; Hantos, Zoltán; Slama, Rémy; Pin, Isabelle; Bayat, Sam (Respiratory research, 2024)
Background Intra-breath oscillometry has been proposed as a sensitive means of detecting airway obstruction in young children. We aimed to assess the impact of early life wheezing and lower respiratory tract illness on lung function, using both standard and intra-breath oscillometry in 3 year old children. Methods History of doctor-diagnosed asthma, wheezing, bronchiolitis and bronchitis and hospitalisation for respiratory problems were assessed by questionnaires in 384 population-based children. Association of respiratory history with standard and intra-breath oscillometry parameters, including resistance at 7 Hz (R 7 ), frequency-dependence of resistance (R 7 − 19 ), reactance at 7 Hz (X 7 ), area of the reactance curve (AX), end-inspiratory and end-expiratory R (R eI , R eE ) and X (X eI , X eE ), and volume-dependence of resistance (ΔR = R eE -R eI ) was estimated by linear regression adjusted on confounders. Results Among the 320 children who accepted the oscillometry test, 281 (88%) performed 3 technically acceptable and reproducible standard oscillometry measurements and 251 children also performed one intra-breath oscillometry measurement. Asthma was associated with higher R eI , R eE , ΔR and R 7 and wheezing was associated with higher ΔR. Bronchiolitis was associated with higher R 7 and AX and lower X eI and bronchitis with higher R eI . No statistically significant association was observed for hospitalisation. Conclusions Our findings confirm the good success rate of oscillometry in 3-year-old children and indicate an association between a history of early-life wheezing and lower respiratory tract illness and lower lung function as assessed by both standard and intra-breath oscillometry. Our study supports the relevance of using intra-breath oscillometry parameters as sensitive outcome measures in preschool children in epidemiological cohorts.